The Development of a Programming-Project Sharing Environment on Virtual Space - Morimoto, T.; Ohira, A.; Yoshimura, M.; Takada, H. (2012 10th International Conference on Creating, Connecting and Collaborating through Computing, 2012)
Recently, there are classes using GUI programming environment such as Squeak Etoys or Scratch in primary education. When children study in such environment, children do not have enough opportunity to view the other's works and show their own work to parents and it is difficult to perform mutual evaluation and review lesson. In this paper, we propose an environment where children or parents can view the children's works on virtual space. It can provide opportunities for children to do mutual evaluation or review the past lesson. We have deployed this system to classes using GUI-programming environment and conducted a questionnaire for children. As a result, seven out of eleven children could view the other's works well. Moreover, eight out of ten children could find a scene in which other children watch the work together, and among these children, six of them viewed this attracting work.